Pemanfaatan Teknologi Digital untuk Menghasilkan Media Pembelajaran: Service Learning bagi Guru Praktek di SMK - Noviarni, Noviarni; Amelia, Rizki; Fitri, Mainar; Nurzena, Nurzena (Tasnim Journal for Community Service, 2025)
This community service activity aims to improve teacher creativity in creating learning media. This activity was carried out at SMK Taruna Pekanbaru. It involved 8 teachers and 8 students. The method used was a service-learning approach that involved students in the community service activity. This approach aims to develop and empower teacher competencies in creating learning media using digital technology. The results of this community service activity in the form of creating learning media through digital technology show that the creativity of practicing teachers has increased in maximizing the function of digital technology as a learning medium, especially in motivating students to think while learning. However, further guidance is needed to improve the quality of teacher learning in the classroom for other subjects.